Climate Risk Management in Agricultural Extension for Ethiopia Reference Guide: 2nd edition - Dinku, Tufa; Hansen, James; Trzaska, Sylwia; Grossi, Amanda; Nsengiyumva, Gloriose; Siebert, Asher; Han, Eunjin; Mangen, Ofelia; Lemma, Esayas; Denboba, Tolessa; Demissie, Teferi; Solomon, Dawit (International Livestock Research Institute, 2024)
This comprehensive Reference Guide is an accompaniment to the abridged Climate Risk Management in Agricultural Extension Handbook. Both the Reference Guide and Handbook are training and reference materials intended to be used during implementation of the Climate Risk Management in Agricultural Extension course. This Reference Guide was designed for Ethiopia’s subject matter specialists (SMS) and extension staff, including development agents (DAs). It may also be used by other actors, such as non-governmental organizations (NGOs) or community-based organizations (CBOs), who work closely with farmers and those who support them. This Reference Guide was designed to provide foundational knowledge on climate and agricultural decision making; and practical tools to analyze climate- related risks, use appropriate weather and climate information to support agricultural decisions, communicate complex climate information effectively with farmers, and integrate climate services into agricultural extension activities. This Reference Guide is organized into four sections corresponding to the four modules of the Climate Risk Management in Agricultural Extension course: Climate Basics, Climate Information Products and Tools Available for Agriculture, Climate- Sensitive Agricultural Decisions, and Integrating Climate Services into Agricultural Extension.